Enrichment of myofibrillar proteins from beef muscle by a simple sequential method - Pighin, Darío Gabriel; Gonzalez, Claudia Beatriz (Wiley, 2022)
A great deal of attention has been paid to the most important proteins of the myofibrillar system – myosin, actin, titin and nebulin – because of their potential role in meat processing. Several methods from different sources were reported for their isolation. However, most of them are complex, tedious and focused on the isolation of one protein at a time. In the present research, these four proteins had been co-enriched simultaneously applying a simple methodology. Myofibrillar proteins extracted from semitendinosus beef muscles were submitted to ammonium sulfate precipitation. Titin and nebulin were precipitated predominantly in the saturation range of 40–60 g/L, and so were myosin heavy chain and actin in the range of 60–100 g/L. Denaturing polyacrylamide electrophoresis and electroelution were employed for the separation and isolation of the proteins of interest from the corresponding salt fractions. Western blot procedure was applied to detect and identify precisely nebulin band.